2013
DOI: 10.1177/0194599813505843
|View full text |Cite
|
Sign up to set email alerts
|

The Subalar Graft and Its Role in Nasal Tip Medialization and Improved Nostril Symmetry

Abstract: While measuring the independent effects of subalar grafting is limited due to contaminant procedures, it can be recognized as a foundation rhinoplasty technique that, in conjunction with septoplasty, provides medialization of the tip in patients with facial asymmetry. Furthermore, aesthetic correction of nostril horizontal dystopia and/or nostril "show" is achieved with the proper application of this technique. This correction represents a unique intervention in rhinoplasty and should be considered a second in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…Although a previous study showed a significant improvement in nasal axis deviation, alar facial angle on base view, and alar facial angle on frontal view with the subalar graft, 2 this study with a larger cohort confirmed these findings. In this cohort, there was also a change in commissure angle on frontal view, although this was a less dramatic change.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although a previous study showed a significant improvement in nasal axis deviation, alar facial angle on base view, and alar facial angle on frontal view with the subalar graft, 2 this study with a larger cohort confirmed these findings. In this cohort, there was also a change in commissure angle on frontal view, although this was a less dramatic change.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies on the subalar graft in 2009 1 and 2013 2 described this technique as a way of correcting asymmetries of the nasal foundation, namely, the maxilla. They found that maxillary asymmetry, best seen on base view, correlated with nasal axis deviation, which is measured on the frontal view.…”
mentioning
confidence: 99%